Environmental sustainability and its antecedents among millennial and Gen-Z students in a public higher learning institution - Radzi, Naziatul Aziah Mohd; Hassan, Suziana; Ibrahim, Mohamad Syahrul Nizam; Saidi, Normaizatul Akma; Hasbollah, Hasif Rafidee (Journal of Asian Scientific Research, 2024)
Numerous segments have long discussed environmental sustainability as a significant topic. This is due to its importance to the environment’s sustainable future. Many studies have focused on the issue of environmental sustainability. As a result, this study will add to the existing literature by identifying the distribution of environmental sustainability antecedents across gender, age, faculties, and area of residence among millennial students from a Malaysian higher education institution. We conducted this study using a cross-sectional research design. We designed a questionnaire and gathered information through an online survey. We used the Structural Equation Modelling Partial Least Square (SEM-PLS) algorithm, specifically SMART PLS 3.2.7, to analyze the data for hypothesis testing. We find that the distribution of knowledge, perceptions, awareness, actions, and initiatives on environmental sustainability remains consistent across gender, age, and area of residence categories. However, other findings from the survey indicated that there is a statistically significant difference in the distribution of perceptions, actions, and initiatives on environmental sustainability across areas of study (faculties). It is evident from the results of the analysis that the context of the study could influence the level of environmental sustainability knowledge, attitude, and behaviour among millennials.